2015
DOI: 10.1186/s10194-015-0572-y
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymic characteristics in pediatric patients with primary headache: a comparison between migraine and tension-type headache

Abstract: BackgroundAlexithymia is a personality construct characterized by difficulties in verbal emotional expression and a limited ability to use one’s imagination. Evidence of alexithymic characteristics was found in adults suffering from headache, while little is known about children. The aim of this study was to establish the prevalence of alexithymia in two different subgroups of children and adolescents suffering from primary headache. We also looked for correlation between alexithymia in children and in their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
1
25
1
3
Order By: Relevance
“…Empirical studies found that alexithymia, i.e., difficulty in identifying and describing feelings and modulating states of emotional arousal (17,18), is associated with both selfharming (19)(20)(21) and psychosomatic behavior (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies found that alexithymia, i.e., difficulty in identifying and describing feelings and modulating states of emotional arousal (17,18), is associated with both selfharming (19)(20)(21) and psychosomatic behavior (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a relationship between alexithymia and different psychiatric disorders, such as depression (Honkalampi et al, 2009;Son et al, 2012;Taylor et al, 1999), eating and body dysmorphic disorders (Fenwick & Sullivan, 2011;Guttman & Laporte, 2002;Karukivi et al, 2010;Speranza et al, 2005), somatoform pain disorder (Burba et al, 2006), migraine (Cerutti et al, 2016;Gatta et al, 2015) and dissociation (Grabe, Rainermann, Spitzer, Gänsicke, & Freyberger, 2000). Moreover, Mennin, Heimberg, Turk, and Fresco (2005) showed that adults who met diagnostic criteria for generalised anxiety disorders (GADs) reported a higher intensity of emotional experience, higher tendency to express negative emotions and less ability to self-soothe after negative emotions than did controls.…”
Section: Introductionmentioning
confidence: 99%
“…The very few studies conducted on clinical samples of children and adolescents found a complex, non‐linear relationship between the emotional functioning of both parents and their offspring. A relationship between alexithymia in mothers and their children was only partially confirmed for samples of patients suffering from primary headache (Gatta et al, ). In samples of female anorexic patients, on the other hand, there was a major role for fathers in the emotional deficits and psychiatric disorders of the daughters (Duclos et al, ).…”
mentioning
confidence: 99%